Research on High-Speed Railway Communication Strategy Based on LIFI Technology - Tingting Chen; Weiwei Hu (Advances in Multimedia)
In order to improve the effect of high-speed railway communication, this paper studies the high-speed railway communication strategy combined with LIFI technology and improves the effect of high-speed railway communication through intelligent communication methods. Moreover, this paper studies the access point allocation problem in indoor LiFi/WiFi hybrid network, fully considers the dynamic change of network load, and introduces a dynamic load balancing algorithm that determines AP allocation in hybrid network based on the data transmission rate as the switching threshold. In addition, this paper proposes two AP allocation methods, such as dynamic switching threshold and minimum data rate constraint, to construct a reliable high-speed railway communication model. The experimental results verify that the high-speed railway communication strategy based on LIFI technology proposed in this paper can effectively improve the high-speed railway communication effect.